Preparation method and application of double-layer hydrogel with fast driving property and efficient recovery property
By using materials such as N-isopropylacrylamide and dopamine in double-layer hydrogels, combined with ultraviolet light and redox initiation technology, the problems of instability and poor recovery of the double-layer hydrogel are solved, and rapid driving is achieved With efficient recovery of double-layer hydrogel, suitable for soft robots and other applications.
Patent Information
- Application Number
- CN202411430031.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
The existing double-layer hydrogel structure is unstable, the driving speed is slow, and it is difficult to restore the original state or the recovery time is long after the driving is completed.
Using a double-layer hydrogel preparation method that combines fast driving and efficient recovery, N-isopropyl acrylamide and N,N-methylene bisacrylamide are dissolved in aqueous sodium alginate solution, and After curing with ultraviolet irradiation, the hydrogel of the functional layer and the control layer is formed by combining the reaction of dopamine hydrochloride and sodium hydroxide solution. The method of redox initiation and ultraviolet light initiation is used to ensure the stability and rapidity of the double-layer hydrogel. response.
It realizes the rapid driving and efficient recovery of the double-layer hydrogel, has strong interface and is not easy to separate, has good photothermal performance and sensing capabilities, and is suitable for soft robots and other fields.
Smart Images

Figure CN119285993A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flexible electronics. Background Art
[0002] Organisms in nature often have flexible, complex and rapid movement behaviors, and their movements are accompanied by the contraction and relaxation of soft muscles. Biological tissues with continuous deformation structures like this have greater degrees of freedom than hard tissues and can bend with high curvature in a limited space. In order to simulate the deformation of such organisms, stimuli-responsive hydrogels have been developed. Hydrogels are three-dimensional cross-linked networks generated by hydrophilic polymers. Stimuli-responsive hydrogels can reversibly deform themselves under external stimuli. Because of their similarities with biological tissues, they are promising candidate materials for soft robots.
[0003] The movement of the actuator depends on the heterogeneous structure of the device. Stacking two hydrogels into a double-layer structure is a simple way to synthesize a heterogeneous structure. However, simply stacking two hydrogels without any treatment will result in an unstable double-layer hydrogel structure that is easy to separate, slow to drive, and difficult to restore to its original state after the drive is completed or a long recovery time. Summary of the invention
[0004] The present invention aims to solve the problems of fragile interface of existing double-layer hydrogel layers, slow driving speed, difficulty in restoring the original state after driving or long recovery time, and further provide a preparation method and application of a double-layer hydrogel with both fast driving and efficient recovery.
[0005] A method for preparing a double-layer hydrogel with both rapid drive and efficient recovery is carried out according to the following steps:
[0006] 1. Dissolve N-isopropylacrylamide and N,N-methylenebisacrylamide in a sodium alginate aqueous solution, stir at room temperature until completely dissolved, add photoinitiator 1173 dropwise, stir at room temperature, pour into a mold and cure with ultraviolet radiation to obtain a hydrogel, immerse the hydrogel in a calcium chloride solution, and then place it in a mold again to obtain a functional layer hydrogel;
[0007] 2. Add dopamine hydrochloride to sodium hydroxide solution, stir at room temperature until the solution turns black, then add acrylamide, N,N-methylenebisacrylamide and ammonium persulfate, stir at room temperature until completely dissolved to obtain a mixed solution, cool the mixed solution in an ice water bath, then take out and add tetramethylethylenediamine dropwise to the cooled mixed solution, pour it into a mold containing a functional layer hydrogel and let it stand to obtain a functional layer hydrogel / control layer hydrogel, thereby completing the preparation method of a double-layer hydrogel with both rapid drive and efficient recovery.
[0008] An application of a double-layer hydrogel with both fast actuation and efficient recovery for fast actuation of actuators.
[0009] The beneficial effects of the present invention are:
[0010] The present invention proposes a method for simply synthesizing a double-layer hydrogel with a stable and strong interface, which has fast drive and recovery, and has good photothermal performance and sensing capabilities. The double-layer hydrogel can achieve stimulus response through polymer chain contraction and photothermal effect under the influence of temperature and near-infrared light, and can quickly recover to its original state after the stimulation ends. This double-layer hydrogel with both fast drive and recovery has important application value in related fields such as soft robots. The details are as follows:
[0011] 1. The present invention adopts a one-pot method to synthesize two layers of hydrogel separately, involving redox initiation and ultraviolet light initiation, which makes the preparation process more flexible and simple. At the same time, the obtained double-layer hydrogel has a strong interface and is not easy to separate, thereby ensuring the good stability of the hydrogel actuator.
[0012] 2. The present invention uses poly N-isopropylacrylamide as the matrix of the functional layer hydrogel, which has good temperature sensitivity. After being cured by ultraviolet light, it has a higher porosity and can absorb water and swell to a saturated state in a short time. At the same time, since the functional layer hydrogel is temperature-sensitive, when the ambient temperature is above its phase transition temperature, it can quickly shrink the polymer chain and discharge part of the water in the hydrogel to achieve the purpose of changing its own volume. Due to the particularity of the functional layer hydrogel structure, it can quickly complete the task of absorbing and discharging water.
[0013] 3. The polydopamine of the present invention gives the control layer hydrogel good photothermal properties. Under near-infrared light irradiation, the hydrogel can convert the absorbed light energy into heat energy to increase its own temperature. When its own temperature is raised above the phase transition temperature of the functional layer hydrogel, the functional layer hydrogel can drain water and reduce its volume to achieve the driving purpose.
[0014] 4. After the precursor solution of the control layer hydrogel of the present invention is treated in an ice water bath, its redox initiation rate is slowed down. When the precursor solution is poured into the template where the functional layer hydrogel is located, the functional layer can absorb more precursor solution of the control layer hydrogel. After the precursor solution is polymerized into a gel, the interface between the two layers of hydrogel is a mixed product of the two, making the interface of the double-layer hydrogel more difficult to separate.
[0015] 5. The present invention introduces sodium alginate and calcium chloride into the functional layer hydrogel, which can not only improve the elasticity of the hydrogel, but also improve the conductivity. The hydrogel can detect electrical signals more sensitively and has broad application prospects in the fields of human motion signal acquisition, health monitoring, machine learning, etc.
[0016] Instruction Manual
[0017] Figure 1 This is a cross-sectional scanning electron micrograph of the functional layer hydrogel / control layer hydrogel prepared in Example 1;
[0018] Figure 2 The X-ray electron energy spectra of the functional layer hydrogel prepared in step 1 of Example 1 and the control layer hydrogel prepared in comparative experiment 2, a is the control layer hydrogel, b is the functional layer hydrogel;
[0019] Figure 3 1 is a tensile test diagram of the functional layer hydrogel / control layer hydrogel, 1 is the functional layer hydrogel / control layer hydrogel prepared in Example 1, 2 is the functional layer hydrogel / control layer hydrogel prepared in Comparative Experiment 1;
[0020] Figure 4 The motion states of the functional layer hydrogel / control layer hydrogel prepared in Example 1 in water baths at different temperatures, a is the bending motion of the hydrogel in a water bath at 60°C, 1 is the functional layer hydrogel, 2 is the control layer hydrogel, b is the hydrogel returning to its original state in a water bath at 25°C, 1 is the functional layer hydrogel, 2 is the control layer hydrogel;
[0021] Figure 5 The curves of the bending angle of the functional layer hydrogel / control layer hydrogel prepared in Example 1 over time, 1 is the bending angle change of the double-layer hydrogel in a 60°C water bath, 2 is the angle change of the double-layer hydrogel in the recovery process in a 25°C water bath;
[0022] Figure 6 To compare the temperature of the control layer hydrogel prepared in Experiment 2 under infrared laser (808nm) irradiation at different powers, 1 is 2.31W / cm 2 , 2 is 1.90W / cm 2 , 3 is 1.46W / cm 2 , 4 is 1.03W / cm 2 , 5 is 0.59W / cm 2 , 6 is 0.18W / cm 2 ;
[0023] Figure 7 The functional layer hydrogel / control layer hydrogel prepared in Example 1 was illuminated by near-infrared light (1.90 W / cm 2 ) pictures under irradiation, a is the actual picture of the double-layer hydrogel, 1 is the functional layer hydrogel, 2 is the control layer hydrogel, and b is the infrared thermal imaging picture of the double-layer hydrogel;
[0024] Figure 8 This is a graph showing the resistance signal changes of the functional layer hydrogel / control layer hydrogel prepared in Example 1 under different strains;
[0025] Fig. 9 This is a graph showing the resistance signal changes of the functional layer hydrogel / control layer hydrogel prepared in Example 1 at different frequencies. DETAILED DESCRIPTION
[0026] Specific implementation method 1: This implementation method is a method for preparing a double-layer hydrogel with both rapid drive and efficient recovery, which is carried out according to the following steps:
[0027] 1. Dissolve N-isopropylacrylamide and N,N-methylenebisacrylamide in a sodium alginate aqueous solution, stir at room temperature until completely dissolved, add photoinitiator 1173 dropwise, stir at room temperature, pour into a mold and cure with ultraviolet radiation to obtain a hydrogel, immerse the hydrogel in a calcium chloride solution, and then place it in a mold again to obtain a functional layer hydrogel;
[0028] 2. Add dopamine hydrochloride to sodium hydroxide solution, stir at room temperature until the solution turns black, then add acrylamide, N,N-methylenebisacrylamide and ammonium persulfate, stir at room temperature until completely dissolved to obtain a mixed solution, cool the mixed solution in an ice water bath, then take out and add tetramethylethylenediamine dropwise to the cooled mixed solution, pour it into a mold containing a functional layer hydrogel and let it stand to obtain a functional layer hydrogel / control layer hydrogel, thereby completing the preparation method of a double-layer hydrogel with both rapid drive and efficient recovery.
[0029] The beneficial effects of this embodiment are:
[0030] This embodiment proposes a method for simply synthesizing a double-layer hydrogel with a stable and strong interface, which has fast drive and recovery, and has good photothermal performance and sensing capabilities. The double-layer hydrogel can achieve stimulus response through polymer chain contraction and photothermal effect under the influence of temperature and near-infrared light, and can quickly recover to its original state after the stimulation ends. This double-layer hydrogel with both fast drive and recovery has important application value in related fields such as soft robots. The details are as follows:
[0031] 1. This embodiment adopts a one-pot method to synthesize two layers of hydrogel separately, involving redox initiation and ultraviolet light initiation, which makes the preparation process more flexible and simple. At the same time, the obtained double-layer hydrogel has a strong interface and is not easy to separate, ensuring the good stability of the hydrogel actuator.
[0032] 2. This embodiment uses poly N-isopropylacrylamide as the matrix of the functional layer hydrogel, which has good temperature sensitivity. After being cured by UV to form a gel, it has a higher porosity and can absorb water and swell to a saturated state in a short time. At the same time, because the functional layer hydrogel is temperature-sensitive, when the ambient temperature is above its phase transition temperature, it can quickly shrink the polymer chain and discharge part of the water in the hydrogel to achieve the purpose of changing its own volume. Due to the particularity of the structure of the functional layer hydrogel, it can quickly complete the task of absorbing and discharging water.
[0033] 3. The polydopamine in this embodiment gives the control layer hydrogel good photothermal properties. Under near-infrared light irradiation, the hydrogel can convert the absorbed light energy into heat energy to increase its own temperature. When its own temperature is raised above the phase transition temperature of the functional layer hydrogel, the functional layer hydrogel can drain water and reduce its volume to achieve the driving purpose.
[0034] 4. In this embodiment, the precursor solution of the control layer hydrogel is treated in an ice water bath, which slows down its redox initiation rate. When the precursor solution is poured into the template where the functional layer hydrogel is located, the functional layer can absorb more precursor solution of the control layer hydrogel. After the precursor solution is polymerized into a gel, the interface between the two layers of hydrogel is a mixed product of the two, making the interface of the double-layer hydrogel more difficult to separate.
[0035] 5. This embodiment introduces sodium alginate and calcium chloride into the functional layer hydrogel, which can not only improve the elasticity of the hydrogel, but also improve the conductivity. The hydrogel can detect electrical signals more sensitively and has broad application prospects in the fields of human motion signal acquisition, health monitoring, machine learning, etc.
[0036] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the mass ratio of sodium alginate in the sodium alginate aqueous solution described in step 1 to the volume ratio of deionized water is 1 g: (0.4-0.6) L; the mass ratio of calcium chloride in the calcium chloride solution described in step 1 to the volume ratio of deionized water is 1 g: (0.8-1.2) L. Others are the same as specific embodiment 1.
[0037] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the mass ratio of N-isopropylacrylamide to N,N-methylenebisacrylamide described in step one is 1:(0.008-0.009); the mass ratio of N-isopropylacrylamide described in step one to sodium alginate in the sodium alginate aqueous solution is 1:(0.0018-0.0020); the mass ratio of N-isopropylacrylamide described in step one to the volume ratio of photoinitiator 1173 is 1g:(17.4-17.7)μL; the mass ratio of the hydrogel described in step one to the volume ratio of the calcium chloride solution is 1g:(3.25-6.50)mL. The rest is the same as specific implementation method one or two.
[0038] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the UV curing described in step 1 is specifically performed under the conditions of a wavelength of 350nm to 370nm and a power of 30W to 50W for 10s to 30s. The rest is the same as specific embodiments 1 to 3.
[0039] Specific implementation example 5: This implementation example is different from specific implementation examples 1 to 4 in that: in step 1, the hydrogel is immersed in a calcium chloride solution for 5 to 8 minutes at room temperature. The rest is the same as specific implementation examples 1 to 4.
[0040] Specific embodiment 6: This embodiment is different from Specific embodiments 1 to 5 in that: the pH of the sodium hydroxide solution in step 2 is 10 to 12; the mass ratio of dopamine hydrochloride in step 2 to the volume ratio of the sodium hydroxide solution is 1 mg: (0.3 to 0.5) mL. Others are the same as Specific embodiments 1 to 5.
[0041] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the mass ratio of acrylamide described in step 2 to the volume ratio of sodium hydroxide solution is 1g:(2-3)mL; the mass ratio of acrylamide described in step 2 to N,N'-methylenebisacrylamide is 1:(0.01-0.03); the mass ratio of acrylamide described in step 2 to ammonium persulfate is 1:(0.03-0.05); the mass ratio of acrylamide described in step 2 to tetramethylethylenediamine is 1g:(0.01-0.02)mL. Others are the same as specific embodiments 1 to 6.
[0042] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step two, the mixed solution is placed in an ice water bath at a temperature of 0°C for cooling for 10 to 15 minutes, then taken out and tetramethylethylenediamine is added dropwise to the cooled mixed solution, stirred for 5 to 8 seconds, and poured into a mold containing a functional layer hydrogel within 1 minute, and allowed to stand for 4 to 8 minutes at room temperature. Others are the same as specific embodiments one to seven.
[0043] Specific embodiment 9: This embodiment differs from Specific embodiments 1 to 8 in that the thickness ratio of the functional layer hydrogel to the control layer hydrogel in the functional layer hydrogel / control layer hydrogel described in step 2 is 1:(0.9-1.1). Other aspects are the same as Specific embodiments 1 to 8.
[0044] Specific implementation method ten: This implementation method is an application of a double-layer hydrogel with both rapid driving performance and efficient recovery performance, which is used to rapidly drive an actuator.
[0045] The following examples are used to verify the beneficial effects of the present invention:
[0046] Embodiment 1:
[0047] A method for preparing a double-layer hydrogel with both rapid drive and efficient recovery is carried out according to the following steps:
[0048] 1. Dissolve N-isopropylacrylamide and N,N-methylenebisacrylamide in a sodium alginate aqueous solution, stir at room temperature until completely dissolved, add photoinitiator 1173 dropwise, stir at room temperature, pour into a mold, and cure under ultraviolet irradiation at a wavelength of 365nm and a power of 50W for 20s to obtain a hydrogel. At room temperature, immerse the hydrogel in a calcium chloride solution for 6min, and then place it in a mold again to obtain a functional layer hydrogel;
[0049] The sodium alginate aqueous solution is specifically obtained by adding sodium alginate to deionized water at a temperature of 90° C. and stirring for 2 hours to dissolve the sodium alginate; the mass ratio of sodium alginate to deionized water in the sodium alginate aqueous solution is 1 g:0.5 L; the mass ratio of calcium chloride to deionized water in the calcium chloride solution is 1 g:1 L;
[0050] The mass ratio of the N-isopropylacrylamide to N,N-methylenebisacrylamide is 1:0.0088; the mass ratio of the N-isopropylacrylamide to sodium alginate in the sodium alginate aqueous solution is 1:0.0019; the mass ratio of the N-isopropylacrylamide to the volume ratio of the photoinitiator 1173 is 1 g:17.7 μL; the mass ratio of the hydrogel to the volume ratio of the calcium chloride solution is 1 g:4.88 mL;
[0051] 2. Add dopamine hydrochloride to sodium hydroxide solution, stir at room temperature for 2 hours until the solution turns black, then add acrylamide, N,N-methylenebisacrylamide and ammonium persulfate, stir at room temperature until completely dissolved to obtain a mixed solution, place the mixed solution in an ice water bath at 0°C to cool for 12 minutes, then take it out and drop tetramethylethylenediamine into the cooled mixed solution, stir for 5s to 8s, and pour it into a mold containing a functional layer hydrogel within 1 minute, let it stand at room temperature for 7 minutes to obtain a functional layer hydrogel / control layer hydrogel, that is, a double-layer hydrogel with both fast drive and efficient recovery.
[0052] The pH of the sodium hydroxide solution is 11; the mass ratio of the dopamine hydrochloride to the sodium hydroxide solution is 1 mg:0.4 mL; the mass ratio of the acrylamide to the sodium hydroxide solution is 1 g:2.5 mL; the mass ratio of acrylamide to N,N'-methylenebisacrylamide is 1:0.02; the mass ratio of acrylamide to ammonium persulfate is 1:0.04; the mass ratio of acrylamide to tetramethylethylenediamine is 1 g:0.015 mL;
[0053] The thickness ratio of the functional layer hydrogel to the control layer hydrogel in the functional layer hydrogel / control layer hydrogel is 1:1.
[0054] Comparative Experiment 1: This comparative experiment is different from Example 1 in that: in step 2, the mixed solution is placed in an ice water bath at 0°C for 12 minutes for cooling; instead, the mixed solution is placed at room temperature, tetramethylethylenediamine is added dropwise, stirred for 5s to 8s, and poured into the mold containing the functional layer hydrogel within 1 minute. Other steps are the same as Example 1.
[0055] Comparative Experiment 2: The difference between this comparative experiment and Example 1 is that: Step 1 is eliminated; Step 2: dopamine hydrochloride is added to the sodium hydroxide solution, stirred at room temperature for 2 hours until the solution turns black, then acrylamide, N,N-methylenebisacrylamide and ammonium persulfate are added, stirred at room temperature until completely dissolved, and a mixed solution is obtained, the mixed solution is placed in an ice water bath at a temperature of 0°C and cooled for 12 minutes, then taken out and tetramethylethylenediamine is added dropwise to the cooled mixed solution, stirred for 5s to 8s, and poured into an empty mold within 1 minute, and allowed to stand at room temperature for 7 minutes to obtain a control layer hydrogel. The rest is the same as Example 1.
[0056] Figure 1This is a cross-sectional scanning electron microscope image of the functional layer hydrogel / control layer hydrogel prepared in Example 1. As can be seen from the figure, the double-layer hydrogel as a whole is composed of three pores of different shapes and distributions. The pore distribution of the control layer is relatively scattered, with a pore size of 38μm to 60μm, and the pore distribution of the functional layer is dense and the pores are 13μm to 17μm. The interface between the control layer and the functional layer presents pores of different shapes and distributions from the two, with pores of 19μm to 28μm. This shows that the double-layer hydrogel prepared in Example 1 does not have an interface layer, but has an obvious transition layer, which enhances the anti-separation ability between the two layers of hydrogel.
[0057] Figure 2 The X-ray electron spectra of the functional layer hydrogel prepared in step 1 of Example 1 and the control layer hydrogel prepared in comparative experiment 2 are shown in Figure a for the control layer hydrogel and Figure b for the functional layer hydrogel. The peaks at 1, 2, and 3 in Figure a come from NH, NC=O, and NC groups, respectively, and the peaks at 1 and 2 in Figure b come from NC=O and NC groups, respectively. It can be seen that the control layer hydrogel contains NH groups from polydopamine, while the functional layer hydrogel does not contain polydopamine or other substances carrying NH groups, proving that the synthesis of the two is successful.
[0058] A ZQ990LB universal tensile testing machine was used, with the sensor set to 10 N, the initial stretching distance set to 22.1 mm, and the stretching speed set to 100 mm / min. Figure 3 The fracture tensile diagram of the functional layer hydrogel / control layer hydrogel, 1 is the functional layer hydrogel / control layer hydrogel prepared in Example 1, and 2 is the functional layer hydrogel / control layer hydrogel prepared in Comparative Experiment 1. As can be seen from the figure, the functional layer hydrogel / control layer hydrogel prepared in Example 1 has a higher fracture strain (148%) and stress (21KPa) than the double-layer hydrogel prepared in Comparative Experiment 1, and it is always a whole, ensuring its stability as a sensor. However, the double-layer hydrogel prepared in Comparative Experiment 1 had one of the two layers of hydrogel broken first during the stretching process, and it lacks integrity.
[0059] Figure 4 The motion states of the functional layer hydrogel / control layer hydrogel prepared in Example 1 in water baths at different temperatures, a is the bending motion of the hydrogel in a water bath at 60°C, 1 is the functional layer hydrogel, 2 is the control layer hydrogel, b is the hydrogel returning to its original state in a water bath at 25°C, 1 is the functional layer hydrogel, 2 is the control layer hydrogel. As can be seen from the figure, the functional layer hydrogel in the double-layer hydrogel gradually expelled its own water and shrunk in a water bath at 60°C, causing the double-layer hydrogel to bend; the functional layer hydrogel in the double-layer hydrogel gradually absorbed water and expanded in a water bath at 25°C, causing the double-layer hydrogel to quickly return to a straight state. This reflects the excellent temperature sensitivity and resilience of the functional layer hydrogel.
[0060] Figure 5 The curves of the bending angle of the functional layer hydrogel / control layer hydrogel prepared in Example 1 over time are shown in Figure 1, where 1 is the bending angle change of the double-layer hydrogel in a 60°C water bath, and 2 is the angle change of the double-layer hydrogel in a 25°C water bath during recovery. As can be seen from the figure, the double-layer hydrogel can bend to about 330° in a 60°C water bath for 30 seconds, and can recover to its original shape in a 25°C water bath for 40 seconds.
[0061] Figure 6 To compare the temperature of the control layer hydrogel prepared in Experiment 2 under infrared laser (808nm) irradiation at different powers, 1 is 2.31W / cm 2 , 2 is 1.90W / cm 2 , 3 is 1.46W / cm 2 , 4 is 1.03W / cm 2 , 5 is 0.59W / cm 2 , 6 is 0.18W / cm 2 As can be seen from the figure, the control layer hydrogel at room temperature is 0.18W / cm 2 ~2.31W / cm 2 Under 808nm near-infrared light irradiation, 2.31W / cm 2 After 480s of irradiation, the temperature rises to 79.7℃; 1.90W / cm 2 After 480s of irradiation, the temperature rises to 66.6℃; 1.46W / cm 2 After 480s of irradiation, the temperature rises to 53.8°C; 1.03W / cm 2 After 480s of irradiation, the temperature rose to 42.7°C; 0.59W / cm 2 After 480s of irradiation, the temperature rises to 32.8°C; 0.18W / cm 2 After irradiation for 480 seconds, the temperature rose to 25.2°C. When the infrared laser was turned off, the hydrogels at all powers returned to room temperature within 460 seconds. The control layer hydrogel showed excellent photothermal properties, and the temperature of the control layer hydrogel could be controlled by controlling the infrared laser power and infrared irradiation time. At the same time, after turning off the infrared laser, the temperature of the control group hydrogel returned to its original state, indicating that the hydrogel can be reused.
[0062] At 808nm near-infrared light (1.90W / cm 2 ) The functional layer hydrogel / control layer hydrogel prepared in Example 1 was irradiated, the distance between the sample and the laser was fixed at 5 cm, and the sample size was 6 mm×6 mm×2 mm. Figure 7 The functional layer hydrogel / control layer hydrogel prepared in Example 1 was illuminated by near-infrared light (1.90 W / cm 2) pictures under irradiation, a is the actual picture of the double-layer hydrogel, 1 is the functional layer hydrogel, 2 is the control layer hydrogel, and b is the infrared thermal imaging picture of the double-layer hydrogel. It can be seen from the actual picture that under the irradiation of infrared light, the functional layer hydrogel of the double-layer hydrogel begins to discharge its own water and its thickness becomes thinner. After the laser is turned off, the functional layer hydrogel begins to absorb the discharged water and returns to its original state after 180s. It can be seen from the infrared thermal imaging picture that the temperature of the double-layer hydrogel continues to rise under the irradiation of infrared light. After the laser is turned off, the temperature of the hydrogel drops and returns to its initial state. It reflects that after the control layer hydrogel is combined with the functional layer, the control layer hydrogel can still perform photothermal conversion normally under infrared laser irradiation, and transfer the high temperature to the functional layer hydrogel, so that the functional layer hydrogel can discharge water and absorb water.
[0063] The ZQ990LB universal tensile testing machine was tested with the Chenhua 660e electrochemical workstation. The sensor was set to 10N, the initial stretching distance was set to 22.1mm, the stretching speed was 100mm / min, and it was set under different tensile strains (10%~50%). Each tensile strain cycle was tested 5 times, and the resistance change value was calculated by the current change over time tested by the It curve. Figure 8 The resistance signal change diagram of the functional layer hydrogel / control layer hydrogel prepared in Example 1 under different strains. As can be seen from the figure, the resistance signal changes stably and significantly under different strains. The resistance change rate is 14.8% under 10% strain, 35.8% under 20% strain, 58.3% under 30% strain, 82.7% under 40% strain, and 104.7% under 50% strain. After 5 cycles of stretching under the same strain, the electrical signal changes are basically stable, reflecting the stability of the sensing signal test of the double-layer hydrogel under different strains.
[0064] The ZQ990LB universal tensile testing machine was tested with the Chenhua 660e electrochemical workstation. The sensor was set to 10N, the initial stretching distance was set to 22.1mm, the stretching speed was 100mm / min~300mm / min (100mm / min corresponds to 0.161Hz, 200mm / min corresponds to 0.303Hz, 300mm / min corresponds to 0.417Hz), and the strain size was 40%. Fig. 9 The resistance signal change diagram of the functional layer hydrogel / control layer hydrogel prepared in Example 1 at different frequencies. As can be seen from the figure, the double-layer hydrogel is loaded and unloaded at different frequencies and cycled five times, and the resistance signal obtained changes stably. The different loading and unloading frequencies can show that the double-layer hydrogel is suitable for different loading and unloading sensing scenarios.
[0065] Repeated experiments using the preparation method of Example 1 can obtain a double-layer structure with a stable interface and electrochemical performance, and a good driving effect.
Claims
1. A method for preparing a double-layer hydrogel with both rapid driving performance and efficient recovery performance, characterized in that It is carried out in the following steps:
1. Dissolve N-isopropylacrylamide and N,N-methylenebisacrylamide in a sodium alginate aqueous solution, stir at room temperature until completely dissolved, add photoinitiator 1173 dropwise, stir at room temperature, pour into a mold and cure with ultraviolet radiation to obtain a hydrogel, immerse the hydrogel in a calcium chloride solution, and then place it in a mold again to obtain a functional layer hydrogel; 2. Add dopamine hydrochloride to sodium hydroxide solution, stir at room temperature until the solution turns black, then add acrylamide, N,N-methylenebisacrylamide and ammonium persulfate, stir at room temperature until completely dissolved to obtain a mixed solution, cool the mixed solution in an ice water bath, then take out and add tetramethylethylenediamine dropwise to the cooled mixed solution, pour it into a mold containing a functional layer hydrogel and let it stand to obtain a functional layer hydrogel / control layer hydrogel, thereby completing the preparation method of a double-layer hydrogel with both rapid drive and efficient recovery.
2. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that The volume ratio of the mass of sodium alginate in the sodium alginate aqueous solution described in step 1 to deionized water is 1g:(0.4-0.6)L; the volume ratio of the mass of calcium chloride in the calcium chloride solution described in step 1 to deionized water is 1g:(0.8-1.2)L.
3. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that The mass ratio of N-isopropylacrylamide described in step one to N,N-methylenebisacrylamide is 1:(0.008-0.009); the mass ratio of N-isopropylacrylamide described in step one to sodium alginate in the sodium alginate aqueous solution is 1:(0.0018-0.0020); the volume ratio of the mass of N-isopropylacrylamide described in step one to the photoinitiator 1173 is 1g:(17.4-17.7)μL; the volume ratio of the mass of the hydrogel described in step one to the calcium chloride solution is 1g:(3.25-6.50)mL.
4. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that The ultraviolet irradiation curing described in step 1 is specifically performed under the conditions of a wavelength of 350nm to 370nm and a power of 30W to 50W, and the ultraviolet irradiation curing is performed for 10s to 30s.
5. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that In step 1, the hydrogel is immersed in a calcium chloride solution at room temperature for 5 to 8 minutes.
6. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that The pH of the sodium hydroxide solution described in step 2 is 10-12; the volume ratio of the mass of dopamine hydrochloride described in step 2 to the sodium hydroxide solution is 1 mg: (0.3-0.5) mL.
7. The method for preparing a double-layer hydrogel with both rapid driving performance and high recovery performance according to claim 1, characterized in that The mass ratio of acrylamide described in step 2 to the volume ratio of sodium hydroxide solution is 1g:(2-3)mL; the mass ratio of acrylamide described in step 2 to N,N'-methylenebisacrylamide is 1:(0.01-0.03); the mass ratio of acrylamide described in step 2 to ammonium persulfate is 1:(0.03-0.05); the mass ratio of acrylamide described in step 2 to tetramethylethylenediamine is 1g:(0.01-0.02)mL.
8. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that In step 2, the mixed solution is placed in an ice water bath at 0°C and cooled for 10 to 15 minutes, then taken out and tetramethylethylenediamine is added dropwise to the cooled mixed solution, stirred for 5 to 8 seconds, and poured into a mold containing a functional layer hydrogel within 1 minute, and allowed to stand at room temperature for 4 to 8 minutes.
9. The method for preparing a double-layer hydrogel with both fast driving performance and high recovery performance according to claim 1, characterized in that The thickness ratio of the functional layer hydrogel to the control layer hydrogel in the functional layer hydrogel / control layer hydrogel described in step 2 is 1:(0.9-1.1).
10. Use of a double-layer hydrogel having both fast driving properties and high recovery properties prepared as claimed in claim 1, characterized in that It is used to drive actuators quickly.